Health planning for goats. (2nd November 2019) - Gascoigne, Emily; Dustan, Ben
Abstract : There is evidence that goat numbers are increasing in the UK in both pet and commercial settings and with that a demand for health planning and veterinary surgeons who are familiar with and comfortable advising keepers. In this article we consider the main challenges for keepers of herds of all sizes including routine procedures, parasites, lameness and some of the obstacles for veterinary surgeons such as the lack of licensed medicines and limited evidence-based medicine breadth.